Asbestos Exposure and Attitudes Toward Occupational Health - Swimmer, Gene; Luce, Sally (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
This paper is concerned with the factors affecting the attitudes of workers who manufacture Asbestos products toward occupational health issues.